2016
DOI: 10.1007/s10096-016-2793-7
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile infection in children: epidemiology and risk of recurrence in a low-prevalence country

Abstract: Clostridium difficile infection (CDI) is increasingly found in children worldwide, but limited data are available from children living in southern Europe. A 6-year retrospective study was performed to investigate the epidemiology, clinical features, treatment, and risk of recurrence in Italy. Data of children with community- and hospital-acquired CDI (CA-CDI and HA-CDI, respectively) seen at seven pediatric referral centers in Italy were recorded retrospectively. Annual infection rates/10,000 hospital admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
2
9
1
1
Order By: Relevance
“…In Europe, the most common bacterial pathogens are Campylobacter , Salmonella spp., enteropathogenic E. coli (EPEC), and enteroaggregative E. coli (EAEC) 5 , 6 . Clostridium difficile (Cd) has emerged as a cause of community-acquired diarrheal illness, but local data report a relatively low burden 7 9 . In Ecuador, sub-Saharan Africa, and South Asia, Shigella is the main agent 3 , 10 .…”
Section: Bacterial Etiology Of Acute Gastroenteritis In Developing Anmentioning
confidence: 99%
“…In Europe, the most common bacterial pathogens are Campylobacter , Salmonella spp., enteropathogenic E. coli (EPEC), and enteroaggregative E. coli (EAEC) 5 , 6 . Clostridium difficile (Cd) has emerged as a cause of community-acquired diarrheal illness, but local data report a relatively low burden 7 9 . In Ecuador, sub-Saharan Africa, and South Asia, Shigella is the main agent 3 , 10 .…”
Section: Bacterial Etiology Of Acute Gastroenteritis In Developing Anmentioning
confidence: 99%
“…The toxin intern produced by this bacterium can cause injury to the mucosa and ultimately bloody stools. 23,24 Breastmilk inhibits the growth of the bacteria and thus tend to have less severe symptoms than non-breastfed babies In patients with diarrhea, a stool pH level of 5.5 or less or presence of reducing substances indicates carbohydrate intolerance, which is usually secondary to viral illness and transient in nature. 25…”
Section: Discussionmentioning
confidence: 99%
“…In a multivariate analysis, the route of metronidazole showed that the risk was not substantiated with the intravenous route, but the authors reported the lack of difference in the result could be due to the small portion of children who received the intravenous dose. 55 Although no other pediatric comparative studies of recurrence rates between metronidazole and vancomycin exist, there are several adult studies examining the difference. In a 2015 meta-analysis the superiority for vancomycin over metronidazole was significant for initial clinical cure (RR 0.91; 95% CI 0.84-0.98) and sustained cure (RR 0.88; 95% CI 0.82-0.96) rates in the treatment of CDI, whereas recurrence rates and all-cause mortality remained similar.…”
Section: Recurrencementioning
confidence: 99%